2019
DOI: 10.1162/jocn_a_01328
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual and Perceptual Dimensions of Word Meaning Are Recovered Rapidly and in Parallel during Reading

Abstract: A single word (the noun " elephant") encapsulates a complex multidimensional meaning, including both perceptual (" big," " gray," " trumpeting") and conceptual (" mammal," " can be found in India") features. Opposing theories make different predictions as to whether different features (also conceivable as dimensions of the semantic space) are stored in similar neural regions and recovered with similar temporal dynamics during word reading. In this magnetoencephalography study, we tracked the brain activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…However, this only works if an agent that has learned the language has the knowledge of horses, black, white, stripes, and vertical concepts-i.e., via direct experience, not just through linguistic exposure or encyclopedic definitions. These claims are further backed up by neuroscience research that showed that neural assemblies encode concrete content words (i.e., words that denote visual objects) and verbs (i.e., words that denote actions) are learned and represented in different brain regions (Pulvermüller, 1999;Borghesani et al, 2019). Rogers et al (2020) provides a recent primer and overview of research that has attempted to uncover strengths and weaknesses of BERT and related language models (so-called BERTology).…”
Section: Related Workmentioning
confidence: 99%
“…However, this only works if an agent that has learned the language has the knowledge of horses, black, white, stripes, and vertical concepts-i.e., via direct experience, not just through linguistic exposure or encyclopedic definitions. These claims are further backed up by neuroscience research that showed that neural assemblies encode concrete content words (i.e., words that denote visual objects) and verbs (i.e., words that denote actions) are learned and represented in different brain regions (Pulvermüller, 1999;Borghesani et al, 2019). Rogers et al (2020) provides a recent primer and overview of research that has attempted to uncover strengths and weaknesses of BERT and related language models (so-called BERTology).…”
Section: Related Workmentioning
confidence: 99%
“…We further also showed, here, that these dimensions are represented also separately, in those brain regions that represent the perceptual features when the objects are physically presented, using a distance code adapted to the lower 1-dimensional space that define each perceptual feature. Interestingly, Borghesani et al 2018…”
Section: Sensory Regions Represent Distances Travelled Along Separatementioning
confidence: 99%
“…Word meaning is a frequently-discussed concept (e.g., Austin, 1962;Clark & Gerrig, 1983;Chandler, 1995;Galántai, 2002;Fawcett, 2007;Vahid Dastjerdi, 2011;Vitello & Rodd, 2015;Armstrong & Plaut, 2016;Jurko, 2017;Borghesani, 2019;Ke, 2019;Butler, 2020;Chen, 2020;Rodd, 2020) and perception of lexical meaning and choices of words with justified motivations is always a major and important task in the study of translating practice of moving the meaning of Source Language (SL) to Target Language (TL). But just as Baker (1992) noted, "it is rarely possible to analyze a word, … into distinct components of meaning as language is much more complex to allow that", the complexity of making justifiable choices of words in bilingual translation involves different factors influencing language usages (cf., Duffy et al, 1988;Grace, 1998;Bolger et al, 2008;Yeibo, 2011;Chang, 2018 etc.).…”
Section: The Features Of Logical Meaning Extensionsmentioning
confidence: 99%